Exercise for Solid Organ Transplant Candidates and Recipients: A Joint Position Statement of the Canadian Society of Transplantation and CAN-RESTORE. Issue 9 (September 2019) - Janaudis-Ferreira, Tania; Mathur, Sunita; Deliva, Robin; Howes, Nancy; Patterson, Catherine; Räkel, Agnès; So, Stephanie; Wickerson, Lisa; White, Michel; Avitzur, Yaron; Johnston, Olwyn; Heywood, Norine; et al.
Abstract : Background: The objectives of this position statement were to provide evidence-based and expert-informed recommendations for exercise training in adult and children solid organ transplant (SOT) candidates and recipients and on the outcomes relevant to exercise training and physical function that should be evaluated in SOT. Methods: We identified randomized controlled trials (RCTs) and systematic reviews of exercise interventions in adult and pediatric SOT candidates and recipients. When RCTs were not available, studies of any design were reviewed. The key recommendations were based on scientific evidence and expert-informed opinion. Results: We recommended that exercise training should be offered in the pre- and posttransplant phase for both adults and children. In adults, exercise training pretransplant was safe, but there was insufficient evidence to provide specific guidelines on the training characteristics. RCTs in adult SOT recipients demonstrated that exercise training improved exercise capacity, lower extremity muscle strength, and health-related quality of life. To obtain benefits, exercise training should be of moderate to vigorous-intensity level, 3–5 times a week for a minimum of 8 weeks. In pediatrics, there is an urgent need for high-quality multicenter clinical trials in the pre- and posttransplant phases. Due to limited evidence, specific recommendations regarding training characteristics could not be provided for pediatrics. Conclusions: The clinical relevance of this position statement is that it provides a key step toward raising awareness of the importance of exercise training in SOT patients among transplant professionals. It also identifies key areas for further research.